Pengaruh Tayangan Drama Korea Itaewon Class terhadap Motivasi menjadi Entrepreneurship - Salma Putri Hadiyani; Zainal Abidin; Wahyu Utamidewi (STKIP PGRI SITUBONDO, 2021)
ABSTRACT: This study aims to determine the effect of the message content of Korean dramas and the influence of the characteristics of the role of Park Saeroyi who works hard in opening a business and doing business in the Korean drama series